Efficacy and safety of daylight photodynamic therapy after tailored pretreatment with ablative fractional laser or microdermabrasion: a randomized, side‐by‐side, single‐blind trial in patients with actinic keratosis and large‐area field cancerization. (10th October 2018) - Wenande, E.; Phothong, W.; Bay, C.; Karmisholt, K.E.; Haedersdal, M.; Togsverd‐Bo, K.
Summary: Background: Physical pretreatments can potentiate the efficacy of daylight photodynamic therapy (dPDT), but clinical comparative studies remain limited. Objectives: Performed in large skin areas with actinic keratoses (AKs) and photodamage, this blinded, randomized clinical trial compared the efficacy and safety of dPDT after tailored skin pretreatment using ablative fractional laser (AFL) or microdermabrasion (MD). Methods: Two ≥ 50‐cm 2 side‐by‐side skin areas were randomized to receive a single treatment with AFL‐dPDT or MD‐dPDT. Pretreatment parameters were tailored according to AK grade and skin constitution to ensure standardized immediate end points. Subsequently, methyl aminolaevulinate was applied, followed by 2‐h daylight exposure. The primary outcome comprised blinded assessment of AK clearance at the 3‐month follow‐up. Results: In 18 patients with 832 AKs, AFL‐dPDT provided significantly higher AK clearance (81% vs. 60%, P < 0·001), led to fewer new AKs ( P < 0·001) and showed superior improvement in dyspigmentation ( P = 0·003) and skin texture ( P = 0·001) vs. MD‐dPDT. Peaking at days 3–6, AFL‐PDT induced more intensified local skin responses ( P = 0·004), including instances of Staphylococcus aureus infection ( n = 3). Patients nonetheless preferred AFL‐dPDT ( P = 0·077), due to lower pretreatment‐related pain ( P = 0·002) and superior cosmesis ( P = 0·035) and efficacy compared with MD‐dPDT. Conclusions: AFL‐dPDT is an effective treatment for patients with AK with extensive field cancerization, although AFL pretreatment is associated with intensified local skin reactions. Abstract : What's already known about this topic? Different physical skin pretreatments have been shown to potentiate the efficacy of daylight photodynamic therapy (dPDT), but comparison studies are lacking. What does this study add? Using tailored pretreatment parameters to obtain standardized immediate end points prior to dPDT, ablative fractional laser provided superior lesional clearance and enhanced rejuvenating effects, but increased local skin reactions compared with pretreatment with microdermabrasion. Ablative fractional laser‐assisted dPDT represents a viable, intensified treatment strategy for patients with multiple actinic keratoses and large areas of photodamaged skin. Linked Editorial: Wolf. Br J Dermatol 2019; 180 :697–698 . Respond to this article